A Critical Review on Vrikka Vikara vis-a-vis Chronic Kidney Disease (CKD) (AYUSHDHARA, 2024)
Vrikka vikara is a disease afflicting Mutravaha srotas. In Ayurveda, Chronic Kidney Disease (CKD) aligns with the concept of Vrikka Vikara, encompassing various Doshas and Dhatus. The description of Vrikka roga is mentioned in Bhaisajya Ratnavali chapter no.93 under Vrikkaroga chikitsa prakaranam. Chronic kidney disease is the collaborative progression of Rasavaha, Raktavaha, Mamsavaha, Medovaha srota dushti which reflects through Mutravaha srotas including Oja dushti. The clinical features of Prameha along with Mutrakricchra, Mutraghata and Vrikka Vikara as a whole resemble with Chronic Kidney Disease (CKD). CKD has emerged as one of the most prominent cause of death and suffering in the 21st century associated with a wide range of complications leading to adverse health outcomes which affects greater than 10% of the general population posing significant risks for major non-communicable diseases like Cardiovascular disease and both Type 1 and Type 2 Diabetes Mellitus. Emphasizing its status as a critical public health issue globally, early detection, and management of CKD are crucial to mitigate its impact on morbidity and mortality.